Biochar alters the soil microbiome and soil function: results of next‐generation amplicon sequencing across Europe. Issue 3 (11th July 2016) - Jenkins, Joseph R.; Viger, Maud; Arnold, Elizabeth C.; Harris, Zoe M.; Ventura, Maurizio; Miglietta, Franco; Girardin, Cyril; Edwards, Richard J.; Rumpel, Cornelia; Fornasier, Flavio; Zavalloni, Costanza; Tonon, Giustino; et al.
Abstract: Wide‐scale application of biochar to soil has been suggested as a mechanism to offset increases in CO2 emissions through the long‐term sequestration of a carbon rich and inert substance to the soil, but the implications of this for soil diversity and function remain to be determined. Biochar is capable of inducing changes in soil bacterial communities, but the exact impacts of its application are poorly understood. Using three European sites [UK SRC, short rotation coppice, French grassland (FR) and Italian SRF, short rotation forestry (IT)] treated with identical biochar applications, we undertook 16S and ITS amplicon DNA sequencing. In addition, we carried out assessments of community change over time and N and P mobilization in the UK. Significant changes in bacterial and community structure occurred due to treatment, although the nature of the changes varied by site. STAMP differential abundance analysis showed enrichment of Gemmatimonadete and Acidobacteria in UK biochar plots 1 year after application, whilst control plots exhibited enriched Gemmataceae, Isosphaeraceae and Koribacteraceae . Increased mobility of ammonium and phosphates was also detected after 1 year, coupled with a shift from acid to alkaline phosphomonoesterase activity, which may suggest an ecological and functional shift towards a more copiotrophic ecology. Italy also exhibited enrichments, in both the Proteobacteria (driven by an increase in the order Rhizobiales ) and the Gemmatimonadetes . No significant change in the abundance of individual taxa was noted in FR, although a small significant change in unweighted UNIFRAC occurred, indicating variation in the identities of taxa present due to treatment. Fungal β diversity was affected by treatment in IT and FR, but was unaffected in UK samples. The effects of time and site were greater than that of biochar application in UK samples. Overall, this report gives a tantalizing view of the soil microbiome at several sites across Europe and suggests that although application of biochar has significant effects on microbial communities, these may be small compared with the highly variable soil microbiome that is found in different soils and changes with time.